2015
DOI: 10.1007/s10562-015-1552-1
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Synthesis Palladium Supported on Fe3O4@C: An Efficient and Heterogeneous Recyclable Catalyst for One-Pot Reductive Amination of Aldehydes with Nitroarenes in Aqueous Reaction Medium

Abstract: A highly efficient Pd/Fe 3 O 4 @C catalytic system has been developed for direct reductive amination of carbonyl compounds with nitroarenes in aqueous reaction medium. The catalyst was characterized by TEM, XRD, XPS and VSM. It was found that the catalyst showed a high activity for the one-pot direct reductive amination of aldehydes with nitroarenes in the presence of molecular hydrogen at mild temperature. Besides, the catalyst could be recovered in a facile manner from the reaction mixture and recycled six t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Isotope labeling experiments adapted from Ref. [2] Copyright permission from Elsevier Ltd. [52] (Continued) [90] (Continued) [52] (Continued) (Continued) [65] (Continued) exceeding 99% under mild conditions (Table 5, entry 23). [85] This example is beyond the scope of secondary amine synthesis, which is in the core of the current review, but could be considered as an one of the important synthesis methods.…”
Section: Figure 11mentioning
confidence: 99%
See 2 more Smart Citations
“…Isotope labeling experiments adapted from Ref. [2] Copyright permission from Elsevier Ltd. [52] (Continued) [90] (Continued) [52] (Continued) (Continued) [65] (Continued) exceeding 99% under mild conditions (Table 5, entry 23). [85] This example is beyond the scope of secondary amine synthesis, which is in the core of the current review, but could be considered as an one of the important synthesis methods.…”
Section: Figure 11mentioning
confidence: 99%
“…[52] The reaction time was also quite short over Pd-Fe 3 O 4 /SiO 2 (ethylene diamine), 2.5 h [52] in comparison to Pd/Fe 3 O 4 /C for which 8 h was required (Table 7, entry 10, Table S2, entry 10). [90] Moreover, separation and recycle was reported to be facile. Analogously Pd/Fe 3 O 4 -NH 2 /starch (Pd@Fe 3 O 4 -NH 2 -starch) catalyst with the average diameter of Pd particles of 8.4 nm was efficient in benzaldehyde amination with nitrobenzene giving 93% yield at 25°C in the ethanol-water mixture under hydrogen atmosphere already after 2 h (Table 7, entry 9, Table S2, entry 9).…”
Section: Catalyst Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li’s research group prepared other core–shell Fe 3 O 4 @C nanoparticles (of 160 nm in diameter) having a carbon layer coating of 10 nm in thickness onto which Pd NPs of 3–8 nm in size were homogeneously dispersed (Pd/Fe 3 O 4 @C) [ 65 ]. These nano materials represent a rare example of catalysts active for DRA performed in water.…”
Section: Metal-catalyzed One-pot Reductive Amination Reactionmentioning
confidence: 99%
“…In the last decade, numerous other catalytic systems were developed based on supported palladium (Sydnes et al, 2008;Sreedhar et al, 2009;Dell'anna et al, 2011;Wei et al, 2013;Zhou et al, 2015;Sharma et al, 2017), platinum (Hu et al, 2011;Cirujano et al, 2013), rhodium (Huang et al, 2015), iridium Pintado-Sierra et al, 2013;Sui et al, 2017), ruthenium (Del Pozo et al, 2012), silver (Artiukha et al, 2017), and gold (Yamane et al, 2009;Artiukha et al, 2015) nanoparticles. Heterobimetallic systems such as Pd-Ag (Li et al, 2013;Chen et al, 2015), Pd-Au (Cho et al, 2018;Yin et al, 2018), Ni-Pd (Nişanci et al, 2015), and Rh-Co (Park and Chung, 2015) were also shown to be efficient catalysts for the reductive alkylation of nitro compounds.…”
Section: Intermolecular Reductive Amination Of Aldehydes and Ketones mentioning
confidence: 99%